(3x + 20x + 8x) - 6 This is wrong as your next question indicates.

But where do i put the 12?

It helps in simplifying to use equations. And when you are first practicing with a new idea, it greatly helps to do exactly one step at a time.

$3x + 4(3 + 5x) + 2(4x - 3) = 3x + (4 * 3) + (4 * 5x) + 2(4x - 3) =$

**Distributive property.**
$3x + 12 + 20x + 2(4x - 3) = 3x + 12 + 20x + (2 * 4x) + \{2 * (-\ 3)\} =$

**Distributive property again.**
$3x + 12 + 20x + 8x - 6 =$

**You were fine up to here. **
$3x + 20x + 12 + 20x + 8x - 6 =$

**Commutative property of addition.**
$3x + 20x + 8x + 12 - 6 =$

**Commutative property of addition again.**
Now what?